Correction: Gómez-Cruz et al. Valorisation of Exhausted Olive Pomace by an Eco-Friendly Solvent Extraction Process of Natural Antioxidants. Antioxidants 2020, 9, 1010 - Irene Gómez-Cruz; Cristóbal Cara; Inmaculada Romero; Eulogio Castro; Beatriz Gullón (MDPI AG, 2021)
The author wishes to make the following correction to this paper [...]